2020
DOI: 10.3390/ph13110390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New 1, 3, 4-Oxadiazole-Incorporated 1, 2, 3-Triazole Moieties as Potential Anticancer Agents Targeting Thymidylate Synthase and Their Docking Studies

Abstract: Thymidylate synthase (TS) has emerged as a hot spot in cancer treatment, as it is directly involved in DNA synthesis. In the present article, nine hybrids containing 1,2,3-triazole and 1,3,4-oxadiazole moieties (6–14) were synthesized and evaluated for anticancer and in vitro thymidylate synthase activities. According to in silico pharmacokinetic studies, the synthesized hybrids exhibited good drug likeness properties and bioavailability. The cytotoxicity results indicated that compounds 12 and 13 exhibited re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The synthetic path of naproxen hybrids 8 – 16 and 19 – 26 are presented in Scheme 1 and Scheme 2 . The key intermediates 4 and 5 were prepared according to the reported methods with little modification [ 30 ]. Firstly, Naproxen 1 was converted into methyl ester 2 by reacting with methanol in presence of concentrated sulphuric acid as catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic path of naproxen hybrids 8 – 16 and 19 – 26 are presented in Scheme 1 and Scheme 2 . The key intermediates 4 and 5 were prepared according to the reported methods with little modification [ 30 ]. Firstly, Naproxen 1 was converted into methyl ester 2 by reacting with methanol in presence of concentrated sulphuric acid as catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our previously reported work to find new leads with potential anticancer activity [29][30][31], we thought to explore naproxen incorporated 1,3,4-oxadiazole derivatives for anticancer potential. To the best of our knowledge, the anticancer effect of naproxen derivatives as EGFR has not been reported yet.…”
Section: Generalmentioning
confidence: 99%
“…These inhibitors induce apoptosis and cause cell cycle arrests by halting deoxythymidine monophosphate, which is responsible for formation of dTTP (a DNA synthesis precursor) [ 22 ]. From the literature, it is reported that 1,3,4-oxadiazole and 1,2,3-triazole derivatives exhibit antiproliferative activity by inhibiting thymidylate synthase [ 23 , 24 , 25 , 26 , 27 , 28 ] ( Figure 1 ). Our research group has been involved in the development of anticancer leads targeting thymidylate synthase.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility and the usefulness of the 1,3,4-oxadiazole scaffold is demonstrated by its use as a core structure in the inhibitors of methionine aminopeptidase (MetAP2) [ 12 ], telomerase [ 13 , 14 ], focal adhesion kinase (FAK) [ 15 ], thymidylate synthase (TS) [ 16 ], glycogen synthase kinase-3 (GSK-3) [ 17 ], and thymidine phosphorylase (TP) [ 18 , 19 ]. The antitumor potency of 1,3,4-oxadiazoles derivatives is also related to their ability to inhibit grow factors such as epidermal growth factor receptor (EGFR) [ 20 , 21 ] or vascular endothelial growth factor (VEGF) [ 22 ], to inhibit tubulin polymerization [ 23 ], histone deacetylases (HDAC) [ 24 , 25 ], or to interact with DNA structures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%